1977
DOI: 10.1007/bf00145769
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility of two populations of Eucalyptus viminalis labill. to iron chlorosis

Abstract: I n comparing two populations of E. viminalis observations indicated that plants of a calcareous population (i) showed a greater yield at high pH, and when subjected to Fe-stress, (ii) took longer to develop chlorosis, (iii) more quickly developed new roots, and (iv) were capable of removing more Fe from solution than were plants of an acid population. Some Fe-stressed plants also appeared to be able to reduce Fe 3+ to Fe 2+, but population differences have not yet been clearly established. Plants from an acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…Population differences in P concentration observed in E. obliqua were similar to those of Ladiges 20,21, who found that plants from an acidic population of E.…”
Section: The Effect Of Ph and Psupporting
confidence: 84%
“…Population differences in P concentration observed in E. obliqua were similar to those of Ladiges 20,21, who found that plants from an acidic population of E.…”
Section: The Effect Of Ph and Psupporting
confidence: 84%
“…Four-week-old seedlings and clonal plants were transferred to flexible plastic tubes ('WG7", Arthur Yates and Co., Cannington WA 6107) containing a 1:1 mixture of steam-sterilized acidwashed sand and vermiculite. Plants were supplied three times weekly with nutrient solution (Ladiges, 1977) supplemented with Osmocote fertilizer granules (Sierra Australia Pty Ltd, Castle Hill, NSW 2154) and were grown in a randomized design in a controlled-temperature glasshouse (25 ±5 C). At between 8 and 10 months plants were transferred to larger tubes ('WGIO', 50x63x230 mm long) after pruning the root system, to encourage new root formation, and lightly pruning the shoot.…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
“…Seed of E. calophylla was surface sterilized with 0.1 % calcium hypochlorite and both species were grown in a sterile acid-washed sand and vermiculite mix (1 :2) in 15 cm pots. Plants were watered twice weekly using a nutrient solution slightly modified from that of LADIGES (1977) which had the following composition (values in mg H): N as NH4NO3, 30; P as NaH2PO4 • 2H2O, 5; K as K2SO4, 10; Ca as CaCl2, 50; Mg as MgSO4 • 7H2O, 20; B as H3BP3, 0.2; Zn as ZnSO4 • 7H2O, 0.1; Mn as MnSO4 • 4H2O, 0.1; Mo as (NH4) 6MoiO24 • 4H2O, 0.5; Cu as CUSO4 • 5H2O, 0.02; Fe as FeEDTA, 2.0; pH 6.2. Solution was applied as half strength for the duration of the experiment.…”
Section: Growth Of Plantsmentioning
confidence: 99%